THE RELATIONSHIP BETWEEN ARM AND WAIST MUSCLE STRENGTH AND THROWING RESULTS IN THE WRESTLING BRANCH OF BANDUNG REGENCY - Islahuddin, Mochamad Fahmi; lengkana, Anggi Setia; Rizal Ahmad Fauzi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This research aims to determine the relationship between arm and waist muscle strength and the wrestling performance results in Bandung Regency. This study uses a quantitative method with a correlational approach. The population of this study consists of 30 wrestling athletes from Bandung Regency, with a sample size of 15 people selected using purposive sampling. The instruments used include measuring the strength of the waist or leg muscles with the back and leg dynamometer test, measuring the strength of the arm muscles with the handgrip dynamometer test, and measuring the waist endurance with the 30-second waist endurance test using a doll as the media. Based on table 4.3, the Pearson correlation test shows that. If the calculated r > table r, then reject HO, which means accepting HI. Whereas if r calculated < r table, then HO is not rejected, which means HI is rejected. Based on the analysis results above, the arm muscle strength obtained a calculated r value of 0.884 > table r value of 0.553 for the throwing result, and the waist muscle strength obtained a calculated r value of 0.785 > table r value of 0.553. Therefore, HO is rejected and HI is accepted, which means there is a relationship between arm and waist muscle strength training and the throwing results in the wrestling branch of the Bandung Regency sports. The author draws conclusions about this research based on the results of the data analysis. Strength of the arm and waist muscles is significantly correlated with the performance of the Bandung Regency wrestling branch. Similarly, there is a significant relationship between the performance of the Bandung Regency wrestling branch and the strength of the waist muscles.